Políticas linguísticas sobre o ensino de língua portuguesa no Brasil: uma relação entre a historicidade e o discurso - Monteiro, Liliane (2021)
The conditions for implementing an educational document are configured as a policy in the elaboration and propagation of schooled knowledge in Brazil. Determined by their own means of production, these official archives set goals for teaching in the light of educational guidelines and skills. In this way, these propositions provide a basis for the country’s evaluative artifacts. In this focus, the current dissertation carries out a discussion about the language competences proposed for the High School modality, contained in the text of the Common National Curriculum Base – Base Nacional Curricular Comum (BNCC). The main objective of the study is to comprehend how language appears in this text, understanding it as a crucial factor for the educational development of all stages of teaching. With the analytical choice of BNCC, its importance is recognized nowadays in order to think about Brazilian educational policies. More than that, this document is comprehended as a representation of a political discourse on teaching. Regarding the theoretical framework of this research, the intermingling of the theories of French Discourse Analysis (DA), addressed by Pêcheux, and the theory of the History of Linguistic Ideas (HIL), addressed by Auroux. It is noteworthy that both theories gain prominence in Brazil from the researcher Orlandi, who proposes a discussion based on the two lines of research. In this game between DA and HIL, an attempt is made to read the BNCC, thinking of the text as a discourse capable of meaning and that is produced from an ideology. Therefore, we identified that this text presents traces from a perspective of integral education and with formative itineraries that modify the educational regime of Brazilian High School.